The Determinants of Audit Opinion in Resilient Firms before and after Covid Pandemic: The Case Study of Tunisian Banks Publishing CSR Information - Wissal, Ben Letaifa; Ichrak , Maamouri; Lotfi, Taleb (Journal of Ecohumanism, 2024)
Purpose - The purpose of this study is to identify the determinants of audit opinion. Design/methodology/approach - We have examined financial statements, and auditor's opinion to particularly note which companies received a qualified/modified opinion contrary to those who had received an unqualified/unmodified opinion. The data was taken from a sample of the 11 listed banks in Tunisia during the critical era of covid from 2018 to 2021. Findings - The results in this report indicate that audit quality has an effect on qualified opinion, meaning if a company is audited by a BIG4 company; it's more likely to receive a qualified audit opinion. CSR also influences audit opinion